ردّ اعتراض الجوجريّ على السّيوطيّ في رسالته: رفع السِّنة في نصب الزِّنَة: لشمس الدّين محمّد بن عبد الله الفارضيّ (981هـــ) (Journal of Academic Research, 2024)
Imam Al-Suyuti wrote a treatise after he was asked about the reason for placing the accusative words mentioned in the noble hadith: “Glory be to God, the number of His creation, Glory be to God, the satisfaction of Himself, Glory be to God, the beauty of His Throne, Glory be to God, the ink of His words,” so he argued that it is in the accusative case. Yes, so Imam Al-Jawjari objected to him and narrated what was in it Aliyah al-Nasab from sayings, then he refuted al-Suyuti’s opinion and its weakness and responded to him in a letter that they did not address, and they were contemporaries, then after their death Imam Shams al-Din al-Faridi came and wrote this letter without a title; In response to Imam Al-Jujri, and he objected to him in the same way the latter objected to Al-Suyuti, and he defeated Al-Suyuti in it. These three letters in their entirety represent a type of composition that is caused by the responses and objections that occur between peers, reaching the point of quarreling.